The Impact of Job Level and Sex Differences on the Relationship Between Life and Job Satisfaction - Kavanagh, Michael J.; Halpern, Michael T. (Academy of Management Journal, 1977)
Questionnaire data were collected from 411 university employees at three job levels to test two hypotheses relative to differences in the relationship between job and life satisfaction for male and females. Comparisons indicated strong differences, primarily for females, between an earlier study and this study for the life-job satisfaction relationships.